Faktor-Faktor yang Berhubungan dengan Kepatuhan Perawat dalam Penggunaan Alat Pelindung Diri (APD) Setelah Masa Pandemi Covid-19 di RSUD Kota Serang - Ida Faridah; Riyana Vini Alvionita (Malahayati Nursing Journal, 2023)
ABSTRACT The high rate of contamination in COVID-19 patients has caused many medics to be exposed to the Covid-19 virus, especially nurses. Lack of clear flow, limited facilities and infrastructure, and the lack of knowledge, attitudes, motivation and supervision are factors related to the lack of compliance with the use of Personal Protective Equipment (PPE) post COVID-19 pandemic. The purpose of this study was to determine the factors related to nurse compliance in the use of Personal Protective Equipment (PPE) post pandemic period at Serang City Hospital in 2002. This research used quasi-experimental design with a pre and post test without control with a cohort research method. With 35 nurses in Serang City Hospital as samples. This study used the Wilcoxon test and the results showed that there was a relationship between knowledge, motivation, attitude, supervision and availability of facilities with nurses' compliance in the use of PPE due to the presence of a 2-tailed Asymp.Sig value 0.05 which indicates that H0 is rejected and Ha is accepted. Keywords: Factors, Compliance, Nurses ABSTRAK Tingginya angka kontaminasi pada pasien covid-19 menyebabkan banyaknya tenaga kesehatan yang terpapar oleh virus covid-19 khususnya perawat. Kurang jelasnya alur, terbatasnya sarana dan prasarana serta minimnya pengetahuan, sikap, motivasi dan supervisi menjadi faktor-faktor yang berhubungan dengan kurang patuhnya penggunaan Alat Pelindung Diri (APD) setelah masa pandemi covid-19. Tujuan dari penelitian ini adalah untuk mengetahui faktor-faktor yang berhubungan dengan kepatuhan perawat dalam penggunaan Alat Pelindung diri (APD) setelah masa pandemi di RSUD Kota Serang Tahun 2022. Desain penelitian yang digunakan dalam penelitian ini adalah quasi eksperiment dengan pre and post-test without control dengan metode penelitian cohort. Dengan sample sebanyak 35 orang perawat di RSUD Kota Serang. Dari penelitian ini didapatkan hasil bahwa ada hubungan antara pengetahuan, motivasi, sikap, supervisi dan ketersediaan fasilitas dengan kepatuhan perawat dalam penggunaan APD yaitu dengan adanya nilai Asymp.Sig 2-tailed 0,05 yang menandakan bahwa H0 ditolak dan Ha diterima. Kata Kunci: Faktor-Faktor, Kepatuhan, Perawat